The role of support and other factors in early breastfeeding cessation: An analysis of data from a maternity survey in England - Oakley, L; Henderson, J; Redshaw, M; Quigley, M (2014)
Background: Although the majority of women in England initiate breastfeeding, approximately one third cease breastfeeding by six weeks and many of these women report they would like to have breastfed for longer.Methods: Data from a survey of women ≥16 years who gave birth to singleton term infants in 2009 in England; questionnaires were completed approximately three months postnatally. Logistic regression was used to investigate the association between postnatal support and other factors, and breastfeeding cessation at 10 days and six weeks. Population attributable fractions (PAFs) were calculated to estimate the relative contribution of breastfeeding support factors to overall breastfeeding cessation at these two time points.Results: Of the 3840 women who initiated breastfeeding and reported timing of breastfeeding cessation, 13% had stopped by 10 days; and of the 3354 women who were breastfeeding at 10 days, 17% had stopped by six weeks. Socio-demographic factors (maternal age, ethnicity, country of birth, deprivation, education) and antenatal feeding intention were all independently associated with breastfeeding cessation at 10 days and six weeks. Women who did not receive feeding advice or support from a parent or peer support group, voluntary organisation, or breastfeeding clinic were more likely to stop breastfeeding by 10 days. Perceived active support and encouragement from midwives was associated with a lower odds of breastfeeding cessation at both 10 days and six weeks. Estimated PAFs suggest that 34-59% of breastfeeding cessations by 10 days could be avoided if more women in the study population received breastfeeding support.Conclusion: Although multiple factors influence a mother's likelihood of continuing breastfeeding, it is clear that socio-demographic factors are strongly associated with breastfeeding continuation. However, there is evidence that breastfeeding support, including that delivered by peer or lay support workers, may have an important role in preventing cessations in the first few weeks. © 2014 Oakley et al.; licensee BioMed Central Ltd.